Tratamento de efluente proveniente da bovinocultura de leite empregando Wetlands construídos de escoamento subsuperficial - Pelissari, Catiane (2013)
The wastewater from the dairy cattle installations, when poorly managed, unleashes environmental impacts. Because of this, it requires the implementation of technological alternatives with a goal of maintaining environmental quality. Alternatively it is highlight the constructed wetlands, which are systems with low operational requirement designed for treatment of wastewater from various origins. The utilization of this technology, which aims to treat wastewater from the dairy cattle, has been intensified since 1998. Nevertheless, in Brazil there are few studies related to this type of wastewater. This study aims evaluating the applicability of constructed wetlands for the treatment of dairy cattle wastewater. In this study it was implanted two units of artificial wetlands post storage tank (area 116 m²), which receives effluent from a dairy production unit (daily production capacity of 140 liters milk). The constructed wetlands were operated in parallel and are characterized by a horizontal flow constructed wetlands - HFCW (surface area of 26.5 m²) and vertical flow constructed wetland (VFCW) (surface area of 14.3 m²). Both filters were excavated in the soil and water proofed, filled with coarse sand (d10 = 0.30 mm and d60 = 0.75 mm) as filter material and planted with macrophyte Typha domingensis Pers. The filters were fed under a hydraulic regime of 3.98 m³/week for HFCW and 4.5m³/week for VFCW. The treated effluent was infiltrated in the soil, through swales constructed in the experiment area. By physico-chemical and biological over 12 months was observed better performance related to the treated effluent in HFCW with average loading removal of 87% of COD, 81% BOD, 90% of SS , 80% TNK 80% NH4-N and 68% PO43-- P, respectively. To VFCW the obtained rates were 70% of COD, BOD of 52%, 70% of SS, 73% of TNK , 81% of NH4-N and 16% of PO43-- P, respectively. It was quantified an average evapotranspiration of 49% in HFCW, whereas the majors evapotranspiration rates occurred in months with higher temperature and in higher macrophytes foliar area. The greatest nutrient content found in the macrophytes occurred simultaneously with the highest growing velocities, which occurred in the beginning of plant development. The foliar tissue of HFCW was responsible for removal of 5.12% of the N load and 3.16% of the P load applied. In VFCW the macrophytes removed 0.88% of the applied N load and 0.30% of the applied P load. From the results obtained in this study recommends the use of constructed wetlands as an alternative technology to the treatment of wastewater originating from the dairy cattle facilities.